Penerapan Teknologi Panel Surya untuk Penerangan dalam Mendukung Green Environment dalam Implementasi Ekonomi Sirkular - Kris Tanto (Jurnal Green Growth dan Manajemen Lingkungan, 2023)
In the face of global trends today, the world is faced with "global uncertainty" where the threat to the food and energy crisis has become more real after the COVID-19 pandemic and the conditions at the time of writing in relation to the war between Russia - Ukraine, the world needs certainty of need for sustainable energy for the survival of human civilization. Commodities from energy sources derived from fossil fuels are becoming increasingly expensive with the embargo against the largest oil and gas producing country in Europe, namely Russia, making world oil and gas prices soar in 2022. Likewise, conditions in Indonesia where the largest non-reversible energy source produced, namely coal for most of our power plants, has also increased due to soaring demand in other parts of the world that lack oil and gas due to the effects of war. So this study looks at and observes directly the application of solar panel technology and innovation with solar energy sources that are converted into electrical energy for lighting needs in the fields of plantations, mining, warehousing and also in the marine sector for the needs of fishing boats. The results of this study indicate a very good level of feasibility in the warehousing and marine business sectors. We can maximize this solar panel because there are abundant sources of sunlight in Indonesia, so that a circular economy will be created in terms of the utilization of energy sources and will end in the creation of a green environment because sunlight is a renewable energy source that is so environmentally friendly and on a large macro scale it also will help the government to reduce subsidies for fuel oil due to use in the marine sector which is very dependent on this energy.